Sebuah Peran Strategis Senapan Serbu Amfibi di Lingkungan Operasi Wilayah Maritim, Pesisir, Bawah Laut, dan Darat dalam Memajukan Teknologi Pertahanan untuk Mendukung Ketahanan Nasional - Nugraha, Dandy; I Nengah Putra; Ade Muhammad; Muhammad Dimas Barazki (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Amphibious Assault Rifles, known for their versatility, play a crucial strategic role in various operating environments, including maritime, coastal, underwater, and land areas. This study investigates their significance in advancing defense technology and contributing to national resilience. These rifles, essential to TNI AL special forces like KomandoPasukan Katak (KOPASKA), excel where traditional firearms fall short, making them indispensable in modern military operations. The research explores how these rifles influence defense technology, enhancing national security and resilience in an ever-evolving security landscape. This study analyzes the role of amphibious assault rifles in amphibious operations to support national resilience, identifies challenges, and considers the defense technology mastery as an effective solution for the development of amphibious assault rifles. A Systematic Literature Review method is employed to gather literature. Challenges encompass defense technology readiness, financial, and manufactur aspects. Strategies involving increased investment, long-term planning, coordination, and human resource development are needed. Development of amphibious assault rifles is proposed to defense technology mastery and support national resilience. The success of defense technology mastery and the development of amphibious assault rifles requires strategic collaboration and the implementation of appropriate solutions.